Systematic Review: Pengaruh Gaya Hidup dan Pengetahuan Masyarakat terhadap Risiko Penyakit Jantung Koroner - Irfan Sazali Nasution; Arini Dwi Rahmadani; Audina, Windi; Sari, Dinda Purnama; Sari, Nailla Deswita (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Coronary heart disease (CHD) is one of the leading causes of death in Indonesia, whose prevalence continues to increase along with changes in lifestyle and the low level of public knowledge about the risk factors of this disease. The purpose of this study was to analyze the influence of lifestyle and the level of public knowledge on the risk of CHD through a systematic review approach. This study used a qualitative descriptive method by analyzing ten scientific articles published between 2020 and 2025. The results of the review showed that unhealthy lifestyles, such as smoking, consumption of foods high in fat and salt, lack of physical activity, and conditions of hypertension and diabetes, significantly increase the risk of CHD. In addition, people's low understanding of a healthy diet, the importance of exercise, and awareness of avoiding risk factors are major barriers to prevention efforts. This study emphasizes the importance of health education and behavior change as key strategies in reducing the incidence of CHD. By increasing public awareness through nutrition education, promotion of healthy lifestyles, as well as the involvement of health workers and educational institutions, it is hoped that a culture of healthy living can be created from an early age as a long-term preventive measure.